KEWENANGAN KOMISI PEMBERANTASA KORUPSI (KPK) PADA PEMERIKSAAN LAPORAN HARTA PARA PEJABAT NEGARA - Noviriska (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The Corruption Eradication Commission (KPK), an institution authorized by law in the Indonesian constitutional system based on the 1945 Constitution to eradicate corruption in a constitutional manner that has duties and authorities independently and is free from the influence of any power based on Law No. 30 of 2002 concerning Corruption Eradication Commission. One of the powers possessed by the Corruption Eradication Commission is the authority to register and examine the wealth reports of state administrators as regulated in Article 7 paragraph 1 letter A of Law No. 19 of 2019 concerning the Corruption Eradication Commission, which until now in reality has not This is not due to laws that have not regulated, but rather the implementation of these rules which are considered still ambiguous in terms of the authority to give these sanctions and the form of sanctions given to state officials who are not disciplined in reporting their assets is still less firm and has not provided a deterrent effect to state officials both before and after taking office. The report on the assets of state officials (LHKPN) is regulated in Article 29 of Law Number 30 of 2002 concerning the Corruption Eradication Commission in conjunction with Article 5 of Law Number 28 of 1999 concerning State Administrators that are Clean and Free from Corruption, Collusion and Nepotism. Sanctions will be given to state officials who do not report their assets both before and after serving as state officials. The sanctions are in the form of administrative sanctions. LHKPN is mandatory for all state administrators, whether in the form of movable objects, tangible or intagible or anything owned by state officials that can be valued in money, including wives and children in their dependents as well as property ownership on behalf of other people obtained both before and after. after taking office. This This clearly hinders the KPK from carrying out its authority in conducting LHKPN. The norms and sanctions as regulated in the law are not clear because it is not clear which authority norms are given to full authority in examining and announcing LHKPN.